Self-Harming Behavior in Borderline Personality Disorder (BPD) - Zawra, Aisya Yara Az; Putri, Erdira Natasya; Damayanti, Fiana; Anggraini, Pratiwi; Amalia, Emmy (Jurnal Biologi Tropis, 2024)
Self-harm behavior is a form of behavior that is carried out to overcome emotional disturbances or emotional pain that is felt by self-harm without any intention to commit suicide. Borderline personality disorder (BPD) is a psychiatric disorder characterized by abnormal patterns of inner experiences and behaviors that affect cognition, emotion, interpersonal functioning, and impulse control. This study was conducted to review various aspects related to self-harm behavior on the borderline personality disorder. . In this bibliography summary we conducted a search on the PubMed database using the search keyword “Borderline Personality Disorder”. The inclusion criteria that we have set include using free full text publications and using English. We also used publications published over the past ten years, as well as publications with relevant discussion of Borderline Personality Disorder. Therefore, appropriate management is required. Some of the treatments include psychoeducation and psychotherapy as well as pharmacological treatment in severe cases. From the 21 literature used, it is stated that self-harm behavior in personality disorders borders on one of the disturbed domains, namely behavioral dysregulation. This dysregulatory behavior can influence CBD sufferers to injure themselves or even attempt suicide.